Electronic test and its relationship with test’s anxiety and academic achievement: Experiment at Qatar University - Alkaabi, Aisha; Altae, Mayamin (Research and Social Study Institute, 2024)
Test anxiety is a real problem that a group of students suffer from in their different stages of education, and it is a source of concern not only for students but also for their whole families. Thus, this paper aims to investigate the impact of electronic tests on students’ anxiety and their academic achievement at Qatar University. A quantitative approach was used to test the hypotheses of this study, and a questionnaire was designed and distributed to the study sample, which consisted of 400 female students at Qatar University. In addition, a quasi-experimental study was adopted, where female students were split into an experimental group with an electronic test as well as a control group using a traditional test. The results showed that there are negative attitudes among students towards electronic tests. The results also found that the electronic tests raised the level of test anxiety among Qatar University students in contrast to the traditional tests. Moreover, the study found that students had higher academic achievement on traditional tests than on electronic tests. Finally, more attention must be directed towards addressing electronic test anxiety, in addition to designing or building remedial counseling programs to reduce levels of electronic test anxiety among female students at Qatar University.